Adequação no perfil das pás de uma turbina para a condição regional dos ventos necessários para a geração de energia: simulação e teste - Celestino Neto, Pedro (Universidade Federal Rural do Semi-Árido, 2019)
This work consists of a research and data collection on low power DC wind turbines. The application of the aerogener of the UFERSA - campus Mossoró features, this is the BERGEY XL 1.0. In this case, it was sought a possibility of an increase in its capacity without profile. For this, aerodynamic profiles that implement the efficiency of small equipment were sought. As a methodology, it was selected from 21 profiles that require lower wind speed for power generation, in a software called Qbalde, specific for their simulation. This was also compared to the original blade profile. Then a set of parts with the selected profile was fabricated using the resin molding transfer method (RTM). Although it was not possible to carry out the quantitative tests per test time, it was still possible to qualitatively verify the efficiency of the wind turbine with the blades manufactured in relation to the original wind conditions, work
Monografia
Keywords: Aerogerador; Pás; Perfil aerodinâmico; Energia eólica; ENGENHARIAS::ENGENHARIA MECANICA